Recurrent sudden sensorineural hearing loss—A literature review - Bang‐Yan Zhang; Yu‐Chien Wang; Kai‐Chieh Chan (Laryngoscope Investigative Otolaryngology, 2022)
Abstract Objective Sudden sensorineural hearing loss (SSNHL) is one of the few emergent otologic conditions. Although more than half of all patients would benefit from timely treatment, recurrence occasionally develops unexpectedly. The aim of our study is to evaluate the recurrence rate after SSNHL, and present the prognosis after first‐episode and recurrent SSNHL. Methods A literature search was conducted of the PubMed and Embase electronic databases. Results Seven studies with a total of 3781 patients were included, and 96 patients experienced recurrence. The recurrence rate ranged between 1.4% and 17%. The average time to recurrence was about 2 years in most studies. The majority of the studies reported using systemic steroids for treating first‐episode SSNHL, and one study used a plasma expander in patients with recurrent SSNHL. The recovery rate for first‐episode patients was 58%–79%, while that for recurrent SSNHL ranged widely, from 21% to 86%. There were no common risk factors for SSNHL recurrence among the studies, although low‐frequency hearing loss, the presence of tinnitus during follow‐up, and an increased neutrophil‐to‐lymphocyte ratio and platelet‐to‐lymphocyte ratio have been proposed. Conclusion Understanding the recurrence rate, risk factors, and prognosis after recurrence of SSHNL is crucial for comprehensive medical care; in this respect, further prospective studies with long‐term follow‐up may be instructive. Level of Evidence 4